2022
DOI: 10.3389/fcell.2022.963278
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cell-Derived Extracellular Vesicles and Engineered Nanovesicles for Hair Growth: From Mechanisms to Therapeutics

Abstract: Hair loss is one of the most common disorders that affect both male and female patients. Cell-derived nanovesicles (CDVs) are natural extracellular vesicles and engineered nanovesicles that can carry various biologicals materials such as proteins, lipids, mRNA, miRNA, and DNA. These vesicles can communicate with local or distant cells and are capable of delivering endogenous materials and exogenous drugs for regenerative therapies. Recent studies revealed that CDVs can serve as new treatment strategies for hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…DP cells, which originate from mesenchymal components, conventionally release growth factors to induce and maintain the development of HFs, regulate the hair cycle, and regenerate HFs. Therefore, DP cells are considered the key signaling centers [ 7 , 17 ]. In this study, we successfully engineered NVs from fibroblasts and found evidence of the direct role of FB-eNVs in DP cells and HFs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DP cells, which originate from mesenchymal components, conventionally release growth factors to induce and maintain the development of HFs, regulate the hair cycle, and regenerate HFs. Therefore, DP cells are considered the key signaling centers [ 7 , 17 ]. In this study, we successfully engineered NVs from fibroblasts and found evidence of the direct role of FB-eNVs in DP cells and HFs.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies, including our previous studies, have reported that EVs/NVs exert their therapeutic effects on hair growth by activating the Wnt/β-catenin signaling pathways [ 7 ]. BMP2 and LEF1 are the known DP signature genes in mice and humans, respectively [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes are endosomal membrane-derived vesicles, approximately 50–150 nm in size, formed during endocytosis and secreted by almost all types of cells, and are present in large numbers in body fluids such as blood, urine, cerebrospinal fluid, tears, and saliva. Their main constituents are lipids, proteins, and nucleic acids, including microRNAs (miRNAs), messenger RNA (mRNA), and DNA derived from secretory cells transferred to other cells [ 12 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ,…”
Section: Introductionmentioning
confidence: 99%